Radar marine maneuvering target detection via high resolution sparse fractional ambiguity function - Xiaohan YU; Xiaolong CHEN; Jian GUAN; Yong HUANG (Tongxin xuebao)
To solve the problem of fast detection of high maneuvering targets in complex ocean background,a radar target detection algorithm via sparse fractional ambiguity function (SFRAF) was proposed.The sparse Fourier transform (SFT) was introduced after instantaneous autocorrelation function calculation,which combines the advantages of SFT and fractional ambiguity function (FRAF).Therefore,SFRAF has good processing performance on high maneuvering signals and can achieve lower computational complexity.The simulation experiments and the measured data processing results show that compared with classical detection method,the detection performance of maneuvering target can be significantly improved,and compared with FRAF,the proposed method can achieve higher detection efficiency.